RESPONSIBILITY TO PROTECT IN UNITED STATES POLICY TOWARDS IMMIGRANTS IN THE PRESIDENT JOE BIDEN ERA - Setiady, Monica A.; Muharjono, Muharjono (Jurnal Studi Diplomasi dan Keamanan, 2024)
This research aims to analyze United States policies towards immigrants under President Joe Biden that reflect Responsibility to Protect through the fulfillment of immigrants rights. Specifically, this research uses Jack Donnelly’s concept of Universal Human Rights to look at the fulfillment of immigrants human rights and bridge the concept of Responsibility to Protect, as well as Diane Stone’s concept of global public policy to analyze whether the United States’ policies towards immigrants heed international rules and norms that have been agreed upon by the world. With violence becoming an increasing concern in several countries, the United Nations and countries around the world, including the United States, passed the Responsibility to Protect resolution. This resolution advocates an increased role for states and the international community to respect human rights and protect civilian populations of any nationality from mass crimes. This research found that United States policies towards immigrants in the Biden era that reflect the Responsibility to Protect are in the form of canceling controversial policies of the previous era, re-enacting old policies, and new policies that are pro-immigrant, especially towards illegal immigrants who experience crimes against humanity or violence in their home countries.